Electric-Field-Induced Domain Switching and Domain Texture Relaxations in Bulk Bismuth Ferrite - Khansur, Neamul H.; Rojac, Tadej; Damjanovic, Dragan; Reinhard, Christina; Webber, Kyle Grant; Kimpton, Justin A.; Daniels, John E.; Khansur, Neamul Hayet (Journal of the American Ceramic Society, 2015)
Bismuth ferrite, BiFeO3, is an important multiferroic material that has attracted remarkable attention for potential applications in functional devices. While thin films of BiFeO3 are attractive for applications in nanoelectronics, bulk polycrystalline BiFeO3 has great potential as a lead-free and/or high-temperature actuator material. However, the actuation mechanisms in bulk BiFeO3 are still to be resolved. Here we report the microscopic origin of electric-field-induced strain in bulk BiFeO3 ceramic by means of in situ high-energy X-ray diffraction. Quantification of intrinsic lattice strain and extrinsic domain switching strain from diffraction data showed that the strain response in rhombohedral bulk BiFeO3 is primarily due to non-180 degrees ferroelectric domain switching, with no observable change in the phase symmetry, up to the maximum field used in the study. The origin of strain thus differs from the strain mechanism previously shown in thin film BiFeO3, which gives a similar strain/field ratio as rhombohedral bulk BiFeO3. A strong post-poling relaxation of switched non-180 degrees ferroelectric domains has been observed and hypothesized to be due to intergranular residual stresses with a possible contribution from the conductive nature of the domain walls in BiFeO3 ceramics.